Novel anti-inflammatory effects of the IL-1 receptor in kidney myeloid cells following ischemic AKI - Chen, Yanting; Lu, Xiaohan; Whitney, Raeann L.; Li, Yu; Robson, Matthew J.; Blakely, Randy D.; Chi, Jen-Tsan; Crowley, Steven D.; Privratsky, Jamie R. (Frontiers in Molecular Biosciences, 2024)
Introduction: Acute kidney injury (AKI) is one of the most common causes of organ failure in critically ill patients. Following AKI, the canonical pro-inflammatory cytokine interleukin-1β (IL-1β) is released predominantly from activated myeloid cells and binds to the interleukin-1 receptor R1 (IL-1R1) on leukocytes and kidney parenchymal cells. IL-1R1 on kidney tubular cells is known to amplify the immune response and exacerbate AKI. However, the specific role of IL-1R1 on myeloid cells during AKI is poorly understood. The objective of the present study was to elucidate the function of myeloid cell IL-1R1 during AKI. As IL-1R1 is known to signal through the pro-inflammatory Toll-like receptor (TLR)/MyD88 pathway, we hypothesized that myeloid cells expressing IL-1R1 would exacerbate AKI.Methods: IL-1R1 was selectively depleted in CD11c + -expressing myeloid cells with CD11cCre + / IL-1R1 fl/fl (Myel KO) mice. Myel KO and littermate controls (CD11cCre -/ IL-1R1 fl/fl -Myel WT) were subjected to kidney ischemia/reperfusion (I/R) injury. Kidney injury was assessed by blood urea nitrogen (BUN), serum creatinine and injury marker neutrophil gelatinase-associated lipocalin (NGAL) protein expression. Renal tubular cells (RTC) were co-cultured with CD11c + bone marrowderived dendritic cells (BMDC) from Myel KO and Myel WT mice.Results: Surprisingly, compared to Myel WT mice, Myel KO mice displayed exaggerated I/R-induced kidney injury, as measured by elevated levels of serum creatinine and BUN, and kidney NGAL protein expression. In support of these findings, in vitro co-culture studies showed that RTC co-cultured with Myel KO BMDC (in the presence of IL-1β) exhibited higher mRNA levels of the kidney injury marker NGAL than those co-cultured with Myel WT BMDC. In addition, we observed that IL-1R1 on Myel WT BMDC preferentially augmented the expression of anti-inflammatory cytokine interleukin-1 receptor antagonist (IL-1ra/Il1rn), effects that were largely abrogated in Myel KO BMDC. Furthermore, recombinant IL-1Ra could rescue IL-1β-induced tubular cell injury. Discussion: Our findings suggest a novel function of IL-1R1 is to serve as a critical negative feedback regulator of IL-1 signaling in CD11c + myeloid cells to dampen inflammation to limit AKI. Our results lend further support for cell-specific, as opposed to global, targeting of immunomodulatory agents.